Looking at city planning : - Corbusier, Le (Grossman, 1971)
First American edition of the English transation by Eleanor Levieux. Originally published in 1946 under the title: Maniere de Penser L'Urbanisme. Glossy turquoise dust jacket with coloured drawing to front and black and white lettering to front and to spine; good, unclipped, but with some small tears and chips at the upper edges (no paper loss), now mylar protected. Turquoise cloth boards with white lettering to spine; in fine condition. Internally clean and free of any markings, with very light toning and a firm binding. In all, a very nice copy of the American translation of this seminal work, presenting in English "Le Corbusier's ideas on transforming our inhospitable streets, planning parks and parking, solving endemic housing problems." ...